Cysteinyl leukotriene receptor 1 mediates LTD4-induced activation of mouse microglial cells in vitro - Yu Shu-ying; Zhang Xia-yan; Wang Xiao-rong; Xu Dong-min; Chen Lu; Zhang Li-hui; Fang San-hua; Lu Yun-bi; Zhang Wei-ping; Wei Er-qing (Acta Pharmacologica Sinica, 2016)
Shu-ying YU1, 2, Xia-yan ZHANG1, Xiao-rong WANG1, Dong-min XU1, Lu CHEN3, Li-hui ZHANG3, San-hua FANG1, Yun-bi LU1, Wei-ping ZHANG1, Er-qing WEI1, * 1Department of Pharmacology, School of Medicine, Zhejiang University, Hangzhou 310058, China; 2Department of Pharmacology, Hangzhou Pediatric Hospital, Hangzhou 310004, China; 3Hangzhou Key Laboratory of Neurobiology and Department of Pharmacology, School of Basic Medicine, Hangzhou Normal University, Hangzhou 310036, China Aim: To investigate the roles of cysteinyl leukotriene receptors CysLT1R and CysLT2R in leukotriene D4 (LTD4)-induced activation of microglial cells in vitro. Methods: Mouse microglial cell line BV2 was transfected with pcDNA3.1(+)-hCysLT1R or pcDNA3.1(+)-hCysLT2R. The expression of relevant mRNAs and proteins in the cells was detected using RT-PCR and Western blotting, respectively. Phagocytosis was determined with flow cytometry analysis. The release of interleukin-1β (IL-1β) from the cells was measured using an ELISA assay. Results: The expression of CysLT1R or CysLT2R was considerably increased in the transfected BV2 cells, and the receptors were mainly distributed in the plasma membrane and cytosol. Treatment of the cells expressing CysLT1R or CysLT2R with CysLT receptor agonist LTD4 (0.1–100 nmol/L) concentration-dependently enhanced the phagocytosis, and increased mRNA expression and release of IL-1β. Moreover, the responses of hCysLT1R-BV2 cells to LTD4 were significantly larger than those of hCysLT2R-BV2 or WT-BV2 cells. Pretreatment of hCysLT1R-BV2 cells with the selective CysLT1R antagonist montelukast (1 μmol/L) significantly blocked LTD4-induced phagocytosis as well as the mRNA expression and release of IL-1β, whereas the selective CysLT2R antagonist HAMI 3379 (1 μmol/L) had no such effects. Conclusion: CysLT1R mediates LTD4-induced activation of BV2 cells, suggesting that CysLT1R antagonists may exert anti-inflammatory activity in brain diseases. Keywords: leukotriene D4; cysteinyl leukotriene receptor; microglia; phagocytosis; IL-1β; montelukast; HAMI; inflammation; brain ischemia This study was supported by the National Natural Science Foundation of China (81273491, 81072618, and 81173041) and the Zhejiang Provincial Natural Science Foundation (LY12H31010). We thank Dr IC Bruce for critically reading and revising the manuscript. * To whom correspondence should be addressed. E-mail weieq2006@zju.edu.cn Received 2013-05-30 Accepted 2013-08-22